Pengembangan Sistem Pembelajaran Pada Laboratorium Komputer Berbasis Local Area Network Di Smk Negeri 4 Kabupaten Kaur - Supardi, Reno; Sartika, Devi (UNIVED Press, 2020)
The development of information technology has a great influence on human life today. Many of the activities carried out involve technological advances themselves. Likewise, computer network technology continues to move forward along with technological developments. Computer networks are currently an important thing in a company or educational institution, with a computer network the communication activities carried out become easier, more effective, save time and there are many other benefits that can be obtained with a computer network, so that all activities carried out through a computer network that always runs smoothly without interruption, the network must always be monitored or supervised.